The Effect of Milking Time and Post-Harvest Handling on the Quality of Fresh Milk in People Livestock - Putri Fitriananda; Setyo Pertiwi; Irma Isnafia Arief (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Milk composition is essential in determining the quality of milk produced by farmers to meet the SNI 3141.1:2011. This study aimed to analyze and assess the physical, chemical, and biological quality of fresh milk from crossbred dairy cows at different milking times and harvest-postharvest handling. The experimental was designed using 2×2 Factorial Complete Randomized design with six repetitions. The independent variables in this study were milking time, including morning (P1), and afternoon (P2). Handling methods included conventional (V1), and modern (V2). Biplot analysis, and Multi-Criteria Decision-Making (MCDM) using the Analytic Hierarchy Process (AHP) method was performed. Milking time had a significant (p<0.05) on specific gravity, pH, TS, fat content, TSNF, protein, lactose, TPC, and S. aureus, which produced the best value at P1, except fat content. Harvest-postharvest handling had a significant (p<0.05) on pH, TPC, S. aureus, and coliforms, where V2 produced the best values compared to V1. Modern harvest-postharvest handling can reduce the TPC of fresh milk by 32.73%, S. aureus by 43.33%, and coliforms by 40.97% compared to that of conventional methods. Biplot analysis showed proximity between TPC, S. aureus and coliform. AHP optimization showed that morning milking time and modern handling methods are the most optimal combinations for producing best quality of fresh milk.   Keywords: Fresh milk, Harvest-postharvest handling, Milking time, Quality.